Induced regulatory T cells in transplantation tolerance - Chen, Y (2010)
Induced regulatory T cells (iTreg) play an important role in the induction of tolerance to self and non-self antigens. Harnessing their suppressive potential has therapeutic implications for the treatment of autoimmune conditions and transplant rejection. Although the role of TGFβ-conditioned iTreg in natural and therapeutic tolerance is indisputable, their mechanism of action as well as factors that influence their function and stability in vivo remain unclear. Here it is shown that TGFβ-conditioning of T cells in the absence of any Foxp3 expression is insufficient for conferring a suppressive phenotype in vivo, whilst Foxp3 expression is sufficient to enable naïve T cells to become suppressive both in vitro and in vivo. Graft antigen was found to enhance the number of iTreg-derived Foxp3+ cells localising to the draining lymph nodes of recipients, and this was associated with histone modifications at the Foxp3 locus that suggested a stabilisation or 'affirmation' of Foxp3 expression. Finally, iTreg were shown to 'out-compete' naïve T cells in forming clusters with dendritic cells. Activated inflammatory T cells could also 'out-compete' naïve T cells. However, unlike activated T cells, iTreg did not activate interacting DCs to the same extent, and this may potentially be a mechanism of their action in vivo.